Hadith Perspective on the Welfare Rights of Informal Workers: Challenges and Opportunities in the Digital Economy Era - Siregar, Khoirun Nisa (Al-Qarawiyyin: Jurnal Ilmu Ushuluddin, 2025)
This research aims to analyze the hadith perspective regarding the welfare rights of informal workers, focusing on the challenges and opportunities faced in the digital economy era. Using analytical descriptive qualitative methods, this research explores hadith texts that talk about workers' rights, such as justice in wages, humane treatment, and social security, and connects them to the current conditions of informal workers. In the era of the digital economy, informal workers face challenges that include income instability, lack of access to social security, and labor exploitation. On the other hand, new opportunities emerge with digital platforms that enable informal workers to connect directly with global markets. This analysis was carried out by referring to several syarah books, classical hadith commentaries, and relevant contemporary literature. The results of this research show that the welfare values promoted by the hadith are still relevant in facing the challenges of informal workers in the digital era, and can be the basis for fairer and more humane regulations. Thus, this research suggests the need for a comprehensive approach in applying hadith principles to address modern challenges, while taking advantage of the opportunities offered by the digital economy.